Impact of foliar fungi on dogroses - Schwer, Carolin Susanne (2006)
Roses are not only popular ornamentals, but some of the wild species also supply us with food, cosmetics and even medicine. Wild roses of the section Caninae, commonly known as dogroses, are often used for their fruits but may also harbour resistance genes that can be used for breeding healthier ornamentals. However, due to the special so-called Canina-meiosis, inheritance is mainly matroclinal with a comparatively small paternal contribution.Therefore, it is important to know how resistance genes are transmitted to the progeny. Different foliar fungi damage roses, most important are blackspot (Marssonina rosae) and powdery mildew (Sphaerotheca pannosa). Furthermore, rust (Phragmidium spec.) is known to infect roses, and a leafspot-disease called Sphaceloma rosarum has recently become more serious. Two fields with dogroses, one with plants obtained by open pollination in wild populations, and one with plants obtained from intra- and interspecific crosses, were evaluated for blackspot, powdery mildew, rust and leafspots in the autumn of 2005. The data was statistically analysed with Systat 5.2. Additionally, microscopic investigations were conducted to gather more knowledge about the appearance of the diseases on the dogrose species. Interestingly, no symptoms of powdery mildew were found in either field, although the fungus infected wild roses of a different section in a field closeby. The investigated dogrose plants had previously been damaged by powdery mildew, suggesting that the presently achieved tolerance is due to plant age or exterior influences. Surprisingly few symptoms of blackspot were found and they differed considerably from those found on ornamental cultivars, indicating a lower susceptibility. Most important in 2005 was rust, followed by leafspot symptoms. The latter were found to be caused not only by Sphaceloma rosarum, but also by Septoria rosae, a fungus never before noticed at Balsgård. The two leafspot diseases produce similar-looking spots that may vary somewhat depending on the host species, and can be properly discriminated only in a microscope. The rose species vary in their disease susceptibility but there was no evidence of really high levels of resistance. Amount of disease symptoms was mainly matroclinally inherited, but a contribution of the pollen parent was also found. Plants with Rosa rubiginosa as seed parent appear to be the most promising candidates for plant breeding since they performed best for rust and leafspots, and might even be resistant to Septoria-leafspot.